Evolution of the Perlecan/HSPG2 Gene and Its Activation in Regenerating Nematostella vectensis - Warren, Curtis R. (Public Library of Science, 2015)

(untitled) (PLoS One)
The heparan sulfate proteoglycan 2 (HSPG2)/perlecan gene is ancient and conserved in all triploblastic species. Its presence maintains critical cell boundaries in tissue and its large (up to ~900 kDa) modular structure has prompted speculation about the evolutionary origin of the gene. The gene’s conservation amongst basal metazoans is unclear. After the recent sequencing of their genomes, the cnidarian Nematostella vectensis and the placozoan Trichoplax adhaerens have become favorite models for studying tissue regeneration and the evolution of multicellularity. More ancient basal metazoan phyla include the poriferan and ctenophore, whose evolutionary relationship has been clarified recently. Our in silico and PCR-based methods indicate that the HSPG2 gene is conserved in both the placozoan and cnidarian genomes, but not in those of the ctenophores and only partly in poriferan genomes. HSPG2 also is absent from published ctenophore and Capsaspora owczarzaki genomes. The gene in T. adhaerens is encoded as two separate but genetically juxtaposed genes that house all of the constituent pieces of the mammalian HSPG2 gene in tandem. These genetic constituents are found in isolated genes of various poriferan species, indicating a possible intronic recombinatory mechanism for assembly of the HSPG2 gene. Perlecan’s expression during wound healing and boundary formation is conserved, as expression of the gene was activated during tissue regeneration and reformation of the basement membrane of N. vectensis. These data indicate that the complex HSPG2 gene evolved concurrently in a common ancestor of placozoans, cnidarians and bilaterians, likely along with the development of differentiated cell types separated by acellular matrices, and is activated to reestablish these tissue borders during wound healing.